DESAIN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI EKOSISTEM DIKELAS INKLUSI SEKOLAH DASAR - Ronald Frasnyaigu; Bunga Mulyahati; Rapita Aprilia (Postgraduate, University of Mataram, 2023)
One of the multimedia technologies that is increasingly popular today is Augmented Reality (AR) technology. The current phenomenon is that inclusive schools still do not have learning media that accommodate children with special needs to be able to develop in accordance with the planned learning objectives. This research tries to develop a media that involves verbal elements represented by reading texts and nonverbal media in the form of three-dimensional projections simultaneously by utilizing AR technology in inclusive classes. The stages of the research conducted refer to the Bord and Gall development model. Development research is divided into several levels of research, while the level of this research is at level 1. Where at level 1 the research stages of the research are carried out to carry out development without testing the product. This research produces Augmented reality-based learning media design in ecosystem material on the food chain sub-chain in grade V elementary school. Learning media design is carried out based on the stages of exploring potential problems of making deian based on the results of the literature review and the validation process by experts. The conclusion is that augmented relaity learning media can visualize abstract concepts for understanding and the structure of an object model allows Augmented relaity as a more effective media in accordance with the objectives of the learning media